GLRA2 gene mutations cause high myopia in humans and mice. Issue 2 (8th April 2022) - Tian, Qi; Tong, Ping; Chen, Gong; Deng, Meichun; Cai, Tian'e; Tian, Runyi; Zhang, Zimin; Xia, Kun; Hu, Zhengmao
Abstract : Background: High myopia (HM) is a leading cause of blindness that has a strong genetic predisposition. However, its genetic and pathogenic mechanisms remain largely unknown. Thus, this study aims to determine the genetic profile of individuals from two large Chinese families with HM and 200 patients with familial/sporadic HM. We also explored the pathogenic mechanism of HM using HEK293 cells and a mouse model. Methods: The participants underwent genome-wide linkage analysis and exome sequencing. Visual acuity, electroretinogram response, refractive error, optical parameters and retinal rod cell genesis were measured in knockout mice. Immunofluorescent staining, biotin-labelled membrane protein isolation and electrophysiological characterisation were conducted in cells transfected with overexpression plasmids. Results: A novel HM locus on Xp22.2-p11.4 was identified. Variant c.539C>T (p.Pro180Leu) in GLRA2 gene was co-segregated with HM in the two families. Another variant, c.458G>A (p.Arg153Gln), was identified in a sporadic sample. The Glra2 knockout mice showed myopia-related phenotypes, decreased electroretinogram responses and impaired retinal rod cell genesis. Variants c.458G>A and c.539C>T altered the localisation of GlyRα2 on the cell membrane and decreased agonist sensitivity. Conclusion: GLRA2 was identified as a novel HM-causing gene. Its variants would cause HM through altered visual experience by impairing photoperception and visual transmission.